Viscosity and retinal vein thrombosis. - Ring, C P (1976)
Whole-blood and plasma viscosity with haematological and biochemical investigations were measured in 44 patients with retinal vein occlusion. The patients were subdivided on the basis of fluorescein angiographic findings into: 1. Those with large areas of capillary non-perfusion. 2. Those with small areas of capillary non-perfusion. 3. Those with an intact capillary pattern. Capillary non-perfusion in retinal vein occlusion is associated with a higher morbidity owing to the complications of retinal neovascularization. Significantly higher values of whole-blood viscosity, packed cell volume, and yield stress have been found in patients with capillary non-perfusion than in those without. These differences may be of critical importance during the episode of retinal vein occlusion and suggest an aetiological factor in the development of capillary non-perfusion. Higher whole-blood and plasma viscosity values and plasma fibrinogen levels have also been shown in the whole retinal vein occlusion group compared with a control group of 30 individuals. These differences may be a factor in the development of retinal vein occlusion but their precise role is difficult to evaluate. Further biochemical investigations in the vein occlusion group supported the strong association with arterial disease and suggested a higher incidence of biochemical abnormalities in those patients with capillary non-perfusion.